Intravenous Immunoglobulin Therapy in Patients With Painful Idiopathic Small Fiber Neuropathy - Geerts, Margot (Neurology, 2021)
OBJECTIVE: This is the first double-blind randomized controlled trial evaluating the efficacy and safety of IV immunoglobulin (IVIG) vs placebo in patients with idiopathic small fiber neuropathy (I-SFN). METHODS: Between July 2016 and November 2018, 60 Dutch patients with skin biopsy–proven I-SFN randomly received a starting dose of IVIG (2 g/kg body weight) or matching placebo (0.9% saline). Subsequently, 3 additional infusions of IVIG (1 g/kg) or placebo were administered at 3-week intervals. The primary outcome was a 1-point change in Pain Intensity Numerical Rating Scale score at 12 weeks compared to baseline. RESULTS: Thirty patients received IVIG, and 30 received placebo. In both groups, 29 patients completed the trial. In 40% of patients receiving IVIG, the mean average pain was decreased by at least 1 point compared to 30% of the patients receiving placebo (p = 0.588, odds ratio 1.56, 95% confidence interval 0.53–4.53). No significant differences were found on any of the other prespecified outcomes, including general well-being, autonomic symptoms, and overall functioning and disability. CONCLUSIONS: This randomized controlled trial showed that IVIG treatment had no significant effect on pain in patients with painful I-SFN. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT02637700, EudraCT 2015-002624-31. CLASSIFICATION OF EVIDENCE: This study provides Class I evidence that for patients with painful I-SFN, IVIG did not significantly reduce pain compared to placebo.